Possibilities of Prisons Functioning in Support of Public Private Partnership Model - Marek Krzysztof Zając; Alina Zając (Contemporary Economics)
From the end of the third quarter of year 2000 the number of penal individuals crosses the number of places provided for them. Therefore building of many convict prisons is necessary. The problem is if the private enterprises should or can participate in. Publication portrays in small degree the current situation of prison management, the idea of PPP as well as advantages and disadvantages of building prisons in support of Public Private Partnership model.